Generalized nörlund method and convergence acceleration - Meronen, Olga; Tammeraid, Ivar (Mathematical Modelling and Analysis, 2007)
Some propositions on λ‐boundedness for generalized Nörlund method of summability (N, Pn ), where Pn are bounded linear operators from Banach space X into X, are proved. Using these results we have verified some propositions on convergence acceleration by N and several Tauberian remainder theorems for generalized Nörlund method.First Published Online: 14 Oct 2010